2014
DOI: 10.1021/jf404694y
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Metabolism of Piceatannol in Rats

Abstract: Piceatannol (trans-3,3',4,5'-tetrahydroxystilbene), a natural analogue of resveratrol, has multiple biological functions. Nevertheless, piceatannol's biological fate is yet to be determined. In this study, we evaluated the absorption and metabolism of piceatannol in rats. Furthermore, the area under the plasma concentration curves (AUC) and metabolic pathway of piceatannol were compared with those of resveratrol. We determined the plasma concentrations of piceatannol, resveratrol, and their respective metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 34 publications
2
113
0
2
Order By: Relevance
“…23) The particular effect will depend on the structure of the compound, and stilbenes such as resveratrol and piceatannol are polyphenols that show the most promise for beneficial health effects. We previously investigated the absorption and metabolism of piceatannol in rats, 24) and the area under the time-concentration curve for intact piceatannol was two-times higher than that of intact resveratrol. After administration of piceatannol, isorhapontigenin, an O-methyl piceatannol metabolite, was detected in the intact form in rat plasma.…”
Section: Discussionmentioning
confidence: 99%
“…23) The particular effect will depend on the structure of the compound, and stilbenes such as resveratrol and piceatannol are polyphenols that show the most promise for beneficial health effects. We previously investigated the absorption and metabolism of piceatannol in rats, 24) and the area under the time-concentration curve for intact piceatannol was two-times higher than that of intact resveratrol. After administration of piceatannol, isorhapontigenin, an O-methyl piceatannol metabolite, was detected in the intact form in rat plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Isorhapontigenin and rhapontigenin are both forms of O -methyl piceatannol [7]. Resveratrol-3- O -glucuronide, resveratrol-4′- O -glucuronide and resveratrol-3- O -sulfate are metabolites of resveratrol.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, isorhapontigenin and rhapontigenin showed SIRT1 induction effects in THP-1 cells. After intragastric administration of piceatannol, isorhapontigenin was detected in both the intact and conjugated forms, and rhapontigenin was detected only in conjugated form [7]. Therefore, after piceatannol intake, isorhapontigenin could contribute to the upregulation of SIRT1 additively with intact piceatannol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations